2021
DOI: 10.1159/000517196
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Alpha-Blocker Therapy in Patients with Missed Preoperative Diagnosis of Extra-Adrenal Retroperitoneal Paraganglioma Undergoing Resection: A Retrospective Study of 167 Cases at a Single Center

Abstract: <b><i>Introduction:</i></b> Preoperative α-adrenergic blockade is thought to decrease perioperative risks and mortality in surgeries for adrenal pheochromocytoma. However, there are limited data on the efficacy of α-blockers in surgeries for retroperitoneal paragangliomas. The aim of this study was to evaluate the effects of the preoperative α-adrenergic blockade on outcomes in patients undergoing surgery for extra-adrenal retroperitoneal paraganglioma. <b><i>Methods:</i&… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 47 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Nine studies reported the maximum intraoperative systolic blood pressure, involving 879 procedures with preoperative α-blockade and 388 without 23 30 , 35 . No difference was shown in the pooled result between groups: MD=0.98 (−5.06, 7.02) mmHg ( P =0.75, I 2 =40%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine studies reported the maximum intraoperative systolic blood pressure, involving 879 procedures with preoperative α-blockade and 388 without 23 30 , 35 . No difference was shown in the pooled result between groups: MD=0.98 (−5.06, 7.02) mmHg ( P =0.75, I 2 =40%).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported the minimum intraoperative systolic blood pressure, involving 763 procedures with preoperative α-blockade and 215 without 24 27 , 29 , 30 , 35 . The pooled result showed a lower value associated with α-blockade, but the difference was not statistically significant: MD=−4.53 (−11.86, 2.79) mmHg ( P =0.23, I 2 =85%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations